MEMBANGUN MODEL QUALITY WORK OF LIFE YANG KONDUSIF GUNA MENINGKATKAN KINERJA DI LINGKUNGAN INDUSTRI KECIL DAN MENENGAH DI PROPINSI DIY - Audita Nuvriasari (Jurnal Aplikasi Bisnis, 2017)
The purposes of this study are: (1). To identify the implementation of QWL programmes which consist of: work satisfaction, employee involvement and job security in Small Medium Industry, (2). To analysis the differences between theimplementation of QWL programs in Small Industry and Medium Industry, (3).To analysis the influence of the implementation of QWL program to the performance of Small Medium Industry, and (4) to create the conducive QWL Program as a source of competitive advantage in the competition of Small Medium Industry.Using descriptive analysis can be explained that the implementation of QWLprogram which consist of work satisfaction and job security are better in MediumIndustry than Small Industry. It means that work environment, compensation and leadership style is better in Medium Industry than in Small Industry. Medium industry gives more guarantees in job security than in Small Indlstry. Employee Involvement as one of QWL program has the same implementation in Small and Medium Industry. Using inferential analysis can be explained thit: (1). there is a positive influence between work satisfaction and employee involve formance of Small medium Industry, (2) there is no influence betweethe performance of Small Medium Industry, (3) there is a differences between the implementation of QWL Program in Small Industry and Medium Industry, (4). There is a differences between the performance of Small industry and medium industry. The performance in Medium Industry which consists of productivity and employee performance is better than Small Industry.To creare a competitive advantage in small-medium industry, can be developed a conduciveness QWL program as follow; (1). Implementation the effective employee involvement, (2). Job redesign, (3). Innovative reward system, (4). Conductive workplace, (5). Increasing job security, (6). Effective leadership, (7). Human resource development, and (7). Management based Good Corporate Governance.